Determination of elastic stiffness coefficients for spudcan foundations in a spatially varying clayey seabed. (November 2022) - Wang, Xiu Zhe; Yi, Jiang Tao; Sun, Miao Jun; Liu, Fei; Xu, Shi Jie
Highlights: Elastic stiffness and deformation mechanisms in spatially variable soil are studied. The effects of k D / μ s u m, C O V G, θ, embedment depth, and backflow are discussed. Spatial variability changes the soil spatial pattern, thus the elastic stiffness. The spudcan's safety probability will only be 50% if spatial variability is ignored. A matrix algebraic expression may predict stiffness at any given confidence level. Abstracts: Determining the elastic stiffness coefficient of spudcan foundations is a challenging task due to the natural variability of soil properties coupled with the complexity of loading conditions. Uncertainty in the elastic stiffness coefficient is a potential risk factor for the safe and stable operation of offshore jack-up platforms, and there are no guidelines for operators to assess its confidence level. This paper conducted a study on this specific subject using the three-dimensional random finite element method. The influence of soil strength heterogeneity, the coefficient of variation and the scale of fluctuation of the shear modulus, embedment depth and soil backflow on the deformation mechanism and elastic stiffness coefficient of spudcans were systemically discussed. The results suggest that the above parameters, combined with the soil's spatial variability, can alter the deformation mechanism, thereby the elastic stiffness coefficient. If spatial variability is ignored in platform design, the safety probability of spudcans is only 50%. So, a matrix algebraic expression is proposed to accurately predict the elastic stiffness coefficient in spatially variable clay at any given confidence level. The study findings may facilitate incorporating spatial variability into elastic stiffness research and supplement the calculation method in the existing jack-up assessment guidelines.